Stem Cell-Based Tissue Repair - Goradetsky, Raphael;Ed. Schäfer, Richard;Ed (Royal Society of Chemistry, 2011)
The need for customized stem cell therapies for specific conditions will be a major issue in the coming decades. This unique book by experts in the field reviews the subject as it stands today. Its coverage includes: basic and applied stem cell research and history; sources of adult stem cells; a comparison of difficulties in derivation, and the applications of embryonic and adult stem cells. Specific topics dealt with include: -advantages and problems associated with stem cell / matrix interactions -stem cell differentiation -difficulties using stem cells for clinical application -stem cell based tissue engineering - myth or reality -stem cells and immunity -natural biological matrices versus synthetic - biocompatibility and integration -stem cell delivery, labeling, imaging and tracking -bioreactors: 2D and 3D cell culturing for in-vitro studies and for stem cell implantation -ethical and safety issues -Good Manufacturing Practice (GMP)